Incidencia de la cartera atrasada sobre la rentabilidad en Compartamos Financiera de 2018 a 2021 - Angulo Rodríguez, Miguel Ángel (2021)
This work of professional sufficiency shows a summary of my performance within the institution Compartamos Financiera S.A. served as business advisor and group credit manager, from June 2018 to May 2021. In this period, the financial situation of the company is described, the analysis procedure for the placement and monitoring of group credit, and the incidence of technical analysis as business advisor and group credit manager in the prevention of delinquent portfolio on profitability. I find that the strategy of short-frequency calendars of group loans allows maintaining a portfolio in arrears of S/ 0.00, improving the supervision and monitoring process of group loans, thus avoiding a reduction in the profitability of Compartamos Financiera S.A. in S/ 1.12 for each increase in the delinquent portfolio in S/ 1.00.